2006
DOI: 10.1152/japplphysiol.00742.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in normobaric hypoxia in endurance runners. I. Improvement in aerobic performance capacity

Abstract: This study investigates whether a 6-wk intermittent hypoxia training (IHT), designed to avoid reductions in training loads and intensities, improves the endurance performance capacity of competitive distance runners. Eighteen athletes were randomly assigned to train in normoxia [Nor group; n = 9; maximal oxygen uptake (VO2 max) = 61.5 +/- 1.1 ml x kg(-1) x min(-1)] or intermittently in hypoxia (Hyp group; n = 9; VO2 max = 64.2 +/- 1.2 ml x kg(-1) x min(-1)). Into their usual normoxic training schedule, athlete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
100
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 49 publications
16
100
2
2
Order By: Relevance
“…Indeed, Czuba et al (5) affirmed that an intensity of 60-70% of the heart rate reserve is not a sufficient training stimulus and will not lead to improvements in aerobic capacity. Regarding the test time, we measured an increase of 6% in the IHTG, a result in consonance with previous studies (7,17,30) and that disagrees with another study that did not find an increase in this parameter (23). These differences in performance might be influenced by the initial athletic performance level of participants, as well as by the session duration, simulated altitude and intensity of hypoxia training (15).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Indeed, Czuba et al (5) affirmed that an intensity of 60-70% of the heart rate reserve is not a sufficient training stimulus and will not lead to improvements in aerobic capacity. Regarding the test time, we measured an increase of 6% in the IHTG, a result in consonance with previous studies (7,17,30) and that disagrees with another study that did not find an increase in this parameter (23). These differences in performance might be influenced by the initial athletic performance level of participants, as well as by the session duration, simulated altitude and intensity of hypoxia training (15).…”
Section: Discussionsupporting
confidence: 63%
“…Theoretically, IHT can improve aerobic capacity and endurance performance at sea level through a series of adaptive changes, however, studies in the field of IHT are inconclusive (7,31). The results of the present research showed no changes in physiological and performance variables in the experimental groups after the 7 weeks of training.…”
Section: Discussioncontrasting
confidence: 61%
“…Los trabajos previos que comprueban los efectos en el umbral anaeróbico producidos por los programas de IHT aprecian una clara mejora del rendimiento asociado a esta variable y por lo tanto, están en consonancia con los resultados obtenidos en nuestra investigación. Así, Dufour et al(2006) observaron una mejora del 4 % en el umbral anaeróbico en atletas de resistencia de alto nivel después de 12 sesiones de 1 hora de duración al 14.5 % de FIO2. Estos resultados también coinciden con Czuba et al (2011) que observaron mejoras en el umbral anaeróbico de ciclistas élite después de 3 semanas realizando 3 sesiones de 1 hora de duración al 15.2 % del FiO2.…”
Section: Discussionunclassified
“…Meanwhile, new alternatives for traditional altitude training regimes have been proposed, known as "living low and training high", and the effects on endurance performance have been demonstrated extensively in athletes [10][11][12]. Recently, several studies have reported the effects of hypoxia training on physical fitness not only in athletes but also in nonathletes [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%